Kajian kandungan proksimat udang vaname (Litopenaeus vannamei) dari berbagai pemberian probiotik - Fahmi Yudas Bastian; Lukman Hudi; Ida Agustini Saidi; Rahmah Utami Budiandari (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2024)
The purpose of the research to determine the effect of probiotics on the proximate content of vaname shrimp (Litopenaeus vannamei). This Research used CRD (Completely Randomized Design) with treatments including P1: conventional cultivation (without probiotics), P2: Probiotic Bio Lacto, P3: Tricodherma sp, P4: GSO4 Probiotic, P5: Tricodherma sp + Probiotic GSO4, and P6: Tricodherma sp + Probiotic Bio Lacto which was done 3 times. Data were analyzed using ANOVA followed by BNJ 5%. The results showed that giving probiotics to vaname shrimp only significantly affected the fat content, while it had no significant effect on water content, ash content, protein and carbohydrate content. The results of the data obtained on the fat content of the lowest value in the treatment of probiotics GSO4 with a value of 1.16 ± 0.14%, and the highest value in the treatment of probiotics Bio Lacto with a value of 4.18 ± 0.76%.